Design and Development of Artificial Zinc Finger Transcription Factors and Zinc Finger Nucleases to the hTERT Locus - Kimberly A Wilson; Morgan L Chateau; Matthew H Porteus (Elsevier, 2013)
The ability to direct human telomerase reverse transcriptase (hTERT) expression through either genetic control or tunable regulatory factors would advance not only our understanding of the transcriptional regulation of this gene, but also potentially produce new strategies for addressing telomerase-associated disease. In this work, we describe the engineering of artificial zinc finger transcription factors (ZFTFs) and ZF nucleases (ZFNs) to target sequences within the hTERT promoter and exon-1. We were able to identify several active ZFTFs that demonstrate a broadly tunable response when screened by a cell-based transcriptional reporter assay. Using the same DNA-binding domains, we generated ZFNs that were screened in combinatorial pairs in cell-based extrachromosomal single-strand annealing (SSA) assays and in gene-targeting assays using stably integrated constructs. Selected ZFN pairs were tested for the ability to induce sequence changes in a Cel1 assay and we observed frequencies of genomic modification up to 18.7% at the endogenous hTERT locus. These screening strategies have pinpointed several ZFN pairs that may be useful in gene editing of the hTERT locus. Our work provides a foundation for using engineered ZF proteins (ZFPs) for modulation of the hTERT locus.